Game Edukasi Mengenal Sejarah Islam Pada Masa Walisongo Berbasis Multi Platform - Nisa, Khoirun; , Endah Sudarmilah, S.T., M.Eng (2016)
Islam arrived in Indonesia through various intermediaries. One of its dissemination ways was through preaching brought by Walisongo (nine saints). Most of children are bored when learning history because its display on the book is only in the form of written texts which are less interesting. The purpose of this research is to develop a multiplatform-based educative game as an interactive learning media. The methodology of this research is the method of SDLC (System Development Life Cycle) which is derived into a stage of system systematically starting from planning, analysis, design, implementation, testing and caring. The testing of this research uses the testing of black box and the testing of usability using questionnaire for the respondents who had used the educative game. the results of research conducted by the author in "MI Mutual-Help Gentan" based on Islam to students who have not been well studied Islamic history in Walisongo period, as many as 93.7% of students agreed that the game can be used as a medium of learning. Keywords: Walisongo, educative game, construct 2, multiplatform